The Influence of E-wom, Brand Image, and Price on Erigo's Purchase Decision on the Shopee Application - Adinda Salsabilla; Y. Yusuf (Golden Ratio of Mapping Idea and Literature Format, 2026)
Seeing the progress and development of the e-commerce world in Indonesia, which is very dynamic, many local brands must be able to understand and know what digital factors have an impact on increasingly selective consumer behavior. This study seeks to provide an analysis related to the influence of Electronic Word of Mouth (e-WOM) and Brand Image and Price on the purchase decision of Erigo products in the Shopee application through an associative quantitative approach and gathered around 156 respondents in Cirebon Regency by applying the 10-times rule technique. Data was collected from the questionnaire and the use of the Likert scale and analyzed with Structural Equation Modeling (SEM) on the basis of Partial Least Squares (PLS). The results indicate that the acquisition of a value of R² 0.713 is significant if the independent variable describes about 71.3% variation in the purchase decision. Then e-WOM produced a positive and significant effect (O = 0.348; P = 0.009) or that consumer reviews are considered as the dominant factor in building trust and driving purchases. Brand Image also produces positive and significant influence (O = 0.329; P = 0.016), indicates the importance of brand image to increase consumer confidence in Erigo products. However, the price produced a positive and insignificant effect at the level of 5% (O = 0.228; P = 0.064). This result means that digital reputation and brand image have more impact on purchasing decisions than price and make local businesses need to pay attention to online reviews and brand image in providing an increase in competitiveness.